The Passion of Max von Oppenheim : Archaeology and Intrigue in the Middle East from Wilhelm II to Hitler - Lionel Gossman
Born into a prominent German Jewish banking family, Baron Max von Oppenheim (1860-1946) was a keen amateur archaeologist and ethnologist. His discovery and excavation of Tell Halaf in Syria marked an important contribution to knowledge of the ancient Middle East, while his massive study of the Bedouins is still consulted by scholars today. He was also an ardent German patriot, eager to support his country's pursuit of its "place in the sun". Excluded by his part-Jewish ancestry from the regular diplomatic service, Oppenheim earned a reputation as "the Kaiser's spy" because of his intriguing against the British in Cairo, as well as his plan, at the start of the First World War, to incite Muslims under British, French and Russian rule to a jihad against the colonial powers. After 1933, despite being half-Jewish according to the Nuremberg Laws, Oppenheim was not persecuted by the Nazis. In fact, he placed his knowledge of the Middle East and his connections with Muslim leaders at the service of the regime. Ranging widely over many fields - from war studies to archaeology and banking history - The Passion of Max von Oppenheim tells the gripping and at times unsettling story of one part-Jewish man's passion for his country in the face of persistent and, in his later years, genocidal anti-Semitism.